37‐1: Invited Paper: Advances in Neural Holographic Displays for Virtual and Augmented Reality. Issue 1 (28th June 2022) - Gopakumar, Manu; Peng, Yifan; Choi, Suyeon; Kim, Jonghyun; Wetzstein, Gordon
Abstract : Holographic near‐eye displays promise unprecedented capabilities for virtual and augmented reality (VR/AR) systems; they can accurately reproduce focus cues, improve power efficiency, and correct for optical aberrations. However, the image quality achieved by traditional holographic displays is limited, and algorithms for computer‐generated holography (CGH) are slow. In this paper, we review emerging artificial intelligence‐enabled holographic near‐eye displays that promise to solve these long‐standing challenges.